(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Object: The objective of this study was to determine the relationship of the location of the ventricular catheter tip and function of the ventriculoperitoneal shunt. Methods: This prospective observational study included 140 patients from a single institution who underwent a ventriculoperitoneal shunt procedure in which a new ventricular catheter was placed between September, 2013 and September 2016. Data abstracted for each patient included age, sex, diagnosis, site and side of ventricular catheter placement. Postoperative CT scan images were reviewed for accuracy of ventricular catheter placement. Patients were followed up over 2 ½ to 4 ½ years.63 patients were available for follow up. We lost communication with rest of the patients. The relationship of the location of the ventricular catheter tip and function of the ventriculoperitoneal shunt was analyzed in 63 patients. Results: There were 140 patients included in the study; accuracy ventricular catheter tip placement were 55 (39.28%) using freehand technique. VP shunt functioned well in 43 (68.25%) of 63 patients. Among the 43 patients with well functioning shunt ,19 were in accurate group ,7 were in suboptimal group and 17 were in inaccurate group.26 patients (41.27%) had good outcome with normal development and normal IQ Conclusions: Mechanical malfunction and infection are the most significant problems associated with shunts for the treatment of hydrocephalus. Above all, a significant proportion of shunt failure was due to obstruction of the ventricular catheter, and accurate placement of the shunt catheter is highly important to reduce the incidence of shunt malfunction. Bang. J Neurosurgery 2019; 9(1): 16-21